Influence of Eichhornia crassipes and Lemna sp. on the natural diet of Astyanax altiparanae Garutti & Britski, 2000 in the initial stages - Eliana Maria Galdioli; Carmino Hayashi; Claudemir Martins Soares; Telma Soares; Liu Wolff (Acta Scientiarum. Biological Sciences, 2017)
Aiming to study the changes in the diet of Astyanax altiparanae in the early developmental stages, in the presence of Eichhornia crassipes (EC) and Lemna sp. (LM), larvae of Astyanax altiparanae were stocked in eight tanks of 900 L (500 ind. tank-1), four with EC and four with LM covering 50% surface. Tanks were inoculated with plankton and received 3.0 g inorganic fertilizer (NPK-7:14:8) and 1.5 g every week. At every three days, three larvae were taken from each tank, fixed in 4% formaldehyde and grouped into four age classes (I: 6 to 12 days, II:15 to 21 days, III:24 to 30 days; IV:33 to 39 days). The analysis of dominance and frequency of occurrence (FO) of food items indicated that, at this stage, A. altiparanae is generalist. In class I, there was a greater dominance and FO of Lecane bulla and Alona sp. in digestive tracts in the presence of both EC and LM, respectively; and larvae started to consume larger organisms, such as Chironomidae, in other age classes with EC. In the presence of LM, Alona sp. was dominant in class II; Chironomidae, in class III and Centropyxis sp., in class IV. Diatoms have greater FO both in EC and in LM. In class III, with EC, Chironomidae had higher FO, as well as Arcella sp. and Scenedesmus spp. with LM. The highest FO in class IV was found for L. bulla and Scenedesmus spp., with EC and LM, respectively. It can be concluded that EC and LM influenced the diet of Astyanax altiparanae, with alterations according to the availability of organisms and increase in age.